Isomorphism theorems for coalgebras - Mavoungou, Jean-Paul (Annales Mathematicae Silesianae, 2019)
Let F be an endofunctor of a category C. We prove isomorphism theorems for F-coalgebras under condition that the underlying category C is exact; that is, regular with exact sequences. Also, F is not assumed to preserve pullbacks.